Broadband 2 μm fluorescence and energy transfer evaluation in Ho3+/Er3+ codoped germanosilicate glass. (August 2015) - Wei, Tao; Tian, Cong; Cai, Muzhi; Tian, Ying; Jing, Xufeng; Zhang, Junjie; Xu, Shiqing
Abstract: This work reports the broadband 2 μm emission from Ho 3+ /Er 3+ codoped germanosilicate glasses. Spectral components of the 2 μm emission band were analyzed and an equivalent model of four-level system was proposed to describe the 2 μm emission band. The results suggested that Ho 3+ /Er 3+ codoped germanosilicate glass has high effective emission bandwidth (172 nm), large emission cross section (5.18×10 −21  cm 2 ) and gain bandwidth (891×10 −28  cm 3 ), which is a promising candidate for 2 μm laser and amplifier. In addition, energy transfer mechanism between Ho 3+ and Er 3+ ions was investigated based on the measured fluorescence spectra and decay curves of Er 3+ : 4 I11/2 and 4 I13/2 levels. Energy transfer efficiency and microscopic parameters were calculated to evaluate the 2 μm fluorescence. Moreover, a rate equation model between Ho 3+ and Er 3+ ions was developed to elucidate 2 μm fluorescence behaviors. This work might provide useful guide to investigate fluorescence behavior and energy transfer mechanism of rare earth ions. Highlights: Ho 3+ /Er 3+ codoped germanosilicate glasses were prepared. Spectral components of the 2 μm emission band were analyzed. Emission bandwidth, emission cross section and gain bandwidth were calculated. Energy transfer mechanism between Ho 3+ and Er 3+ ions was investigated. A rate equation was developed to elucidate 2 μm fluorescence behaviors.